Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Camargo Tolentino, Alex Raúl (2019)
The present work of professional sufficiency focuses on the study of the company Camposol, a Peruvian company in the agroindustry sector located in northern Peru, an internal strategic analysis of its strengths and weakness and external strategic of its opportunities and threats is made to determine the current situation of the company and propose strategies.